2009
DOI: 10.1007/bf03178330
|View full text |Cite
|
Sign up to set email alerts
|

Essential groups and stability of α-glucosidase ofPenicillium notatum

Abstract: --Glucosidase ( -D-glucoside glucohydrolase, EC 3.2.1.20) was isolated from Penicillium notatum. The enzyme was induced by gibberellic acid (GA 3 ). The GA 3 -mediated increase in the enzyme activity was repressed in presence of abscisic acid, cycloheximide and the antibiotics chloramphenicol, cordycepin, and rifampicin which are inhibitors of protein synthesis. -Glucosidase was purified 440-fold with of 27.8-fold of purification. The enzyme was immobilized using chitosan gel. The optimal pH values were 6.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In a subsequent study, the increased sensitivity of insulin to uptake glucose by costunolide was ascribed to the stimulation of the beta islets to secrete insulin (Li et al, 2004). Regarding the chemical structure of diabetes controlling key enzymes, almost all α-glucosidases are reported to be highly inhibited by sulfhydryl-binding reagents (El-Shora et al, 2009;Faridmoayer and Scaman, 2005). This may explain the potent inhibitory activity of SL-EO against this enzyme.…”
Section: In Vitro α-Amylase and α-Glucosidase Activitymentioning
confidence: 96%
“…In a subsequent study, the increased sensitivity of insulin to uptake glucose by costunolide was ascribed to the stimulation of the beta islets to secrete insulin (Li et al, 2004). Regarding the chemical structure of diabetes controlling key enzymes, almost all α-glucosidases are reported to be highly inhibited by sulfhydryl-binding reagents (El-Shora et al, 2009;Faridmoayer and Scaman, 2005). This may explain the potent inhibitory activity of SL-EO against this enzyme.…”
Section: In Vitro α-Amylase and α-Glucosidase Activitymentioning
confidence: 96%
“…revealed also that sesame oil was more effective in inhibiting α glucosidase compared to α amylase. As mentioned previously concerning the chemical structure of diabetes key enzymes, almost all α-glucosidases are extremely inhibited by sulfhydryl groups-binding reagents[87,88]. Additionally, Su et al reported that oleic acid was a competitive inhibitor of α-glucosidase[89].…”
mentioning
confidence: 86%
“…a-Glucosidase is a crucial enzyme in carbohydrate digestion, breaking down linear and branched isomaltose oligosaccharides to release glucose and causing postprandial hyperglycemia. 77 El-Shora and his team 78 visualized and conrmed the a-glucosidase using SDS-PAE, showing a single band with a molecular weight of 45 kDa.…”
Section: (Esi) †mentioning
confidence: 99%